A tale of two schools: comparing and contrasting Jacobus Fruytier Scholengemeenschap in the Netherlands and Bradford Christian School in England - Pike, Mark (Journal of beliefs and values, 2010)
Drawing primarily upon interview and observation data, the aims, admission policies, and curriculum of two ‘strong’ Christian schools, one in the Netherlands and one in England, are compared and contrasted. Analysis of the beliefs and values of children, parents, and school leaders challenges assumptions about ‘strong’ Christian schools that are shown to be insufficiently discriminating on philosophical and theological grounds. Implications for educational policy are briefly considered.